Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.bone.2008.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of biochemical markers of bone turnover as prognostic indicator of successful osteoporosis therapy

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Author's personal copy EditorialRole of biochemical markers of bone turnover as prognostic indicator of successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 33 publications
1
25
0
2
Order By: Relevance
“…It has been well demonstrated how antiresorptive agents reduce the rate of bone remodeling with a decrease in bone resorption and bone formation markers (9)(10)(11)(12). In the present study we observed the changes in bone markers in patients who were taking two classes of anabolic agents and who had previously been on bisphosphonates.…”
Section: Discussionsupporting
confidence: 50%
“…It has been well demonstrated how antiresorptive agents reduce the rate of bone remodeling with a decrease in bone resorption and bone formation markers (9)(10)(11)(12). In the present study we observed the changes in bone markers in patients who were taking two classes of anabolic agents and who had previously been on bisphosphonates.…”
Section: Discussionsupporting
confidence: 50%
“…A significant association has been reported between the short-term decrease in markers of bone turnover with the use of different antiresorptive agents and gains in BMD. More importantly, significant associations have been reported between the short-term decrease in markers of bone turnover and the reduction in risk of vertebral and nonvertebral fractures with the use of antiresorptive agents (9,11). The correlation between old age and increased fracture risk is well documented in many epidemiologic studies (2,12).…”
Section: Discussionmentioning
confidence: 99%
“…However, this method cannot discriminate between the predominance of bone resorption and formation processes at the microstructural level, and requires a long time to detect structural changes. Increased understanding of bone physiology has led to the discoveries of several bone turnover markers in urine and blood related to bone formation and resorption (Mora et al, 1998;Reginster et al, 2008;Vasikaran et al, 2006;Garnero, 2008;Blumsohn et al, 1994). These bone turnover markers can be used to detect biochemical changes before structural changes occur (Braga de Castro Machado et al, 1999;Raisz et al, 2000).…”
Section: Introductionmentioning
confidence: 96%